Pengetahuan Wanita Usia Subur Tentang Kanker Serviks Dengan Perilaku Pemeriksaan Deteksi Dini Menggunakan IVA - Sitti Mukarramah; Subriah Subriah; Wirawati Amin; Humrah Humrah (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2020)
Cervical cancer is the number one killer of women in the world caused by the Human Papilomma Virus. One of the early detection of cervical cancer by checking Visual Inspection with Acetic Acid (VIA) is a simple way to detect cervical abnormalities. Knowledge of cervical cancer is one of the factors influencing WCBA behavior in conducting VIA examinations. This study aims to determine the relationship between WUS knowledge on cervical cancer with early detection examination behavior using VIA in Maradekaya Village. The research sample was 59 respondents with random sampling technique and a cross-sectional research design. The results showed that the respondents' knowledge about cervical cancer was included in the